A generic framework for decomposing block cipher structure with secret components. (August 2021) - Zhang, Jiyan; Cui, Ting; Jin, Chenhui
Abstract: In this paper, we present a generic framework for decomposing block cipher structure with secret components. The generic framework is based on the zero-correlation linear cryptanalysis and exploits clusters of zero-correlation linear hulls to establish a system of equations to recover the secret components. In order to solve such a system, we convert the operations into the field of real numbers. By utilizing the coordinate partition technique, both the time and data complexity will be mitigated to make the framework more competitive. We apply the framework to the Feistel structure with SP-type round functions and both the attack rounds and complexity perform better than previous results. Finally, we apply the proposed framework to the Type-1 Feistel structure to demonstrate its generality and improve the previous results against such structure. Our work provides further insights into the security of block cipher structure with secret components.